1991
DOI: 10.1016/0021-9517(91)90227-u
|View full text |Cite
|
Sign up to set email alerts
|

A chemisorption and XPS study of bimetallic Pt-Sn/Al2O3 catalysts

Abstract: Bimetallic Pt-Sn/AlzO3 catalysts with nominally 1 wt% Pt and varying tin contents (0-3.25 wt%) prepared by coimpregnation of nonporous Degussa alumina were characterized by chemisorption of H2, 02, and CO at room temperature. The surface compositions and oxidation states of the reduced catalysts were tracked by XPS. Addition of tin to Pt resulted in significant differences in the gas uptake characteristics of the three adsorbates. Both H2 and CO showed an initial increase in gas uptake with addition of small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(60 citation statements)
references
References 48 publications
10
47
2
1
Order By: Relevance
“…Because of easier referencing in ESCA technique, from the binding energy of the Sn 3d 5 peak studies conclude that the lowest oxidation state of tin present on alumina is Sn 2+ [46,47,49]. Our observations of Sn supported on mixed oxide correlate well with the mentioned observations of Sn supported on alumina, as no change in the oxidation state of Sn is visible.…”
Section: Sn/mg Ratio Sample Ptsn-1supporting
confidence: 80%
See 1 more Smart Citation
“…Because of easier referencing in ESCA technique, from the binding energy of the Sn 3d 5 peak studies conclude that the lowest oxidation state of tin present on alumina is Sn 2+ [46,47,49]. Our observations of Sn supported on mixed oxide correlate well with the mentioned observations of Sn supported on alumina, as no change in the oxidation state of Sn is visible.…”
Section: Sn/mg Ratio Sample Ptsn-1supporting
confidence: 80%
“…Because of similar chemical shifts of the Sn 2+ and Sn 4+ peaks, it is not possible to distinguish between these two oxidation states of tin by examining the shape of the peaks [45]. However, it would be possible to see changes in the peak shape if the oxidation state of Sn would change between Sn 2+/4+ and Sn 0 , as the chemical shift of Sn 3d in tin oxides compared to pure tin is usually reported to be in the region of 1.5-1.8 eV [45][46][47]. A larger separation between oxidised and metallic tin has been observed in supported Pt-Sn catalysts.…”
Section: Sn/mg Ratio Sample Ptsn-1mentioning
confidence: 99%
“…Although overall selenium concentration in the catalyst is low, and molar ratio Se/Pd is about 1:7, the surface metal layer is enriched with low melting selenium similar to Sn-Pt system [27,28]. Therefore, the surface layer of modified palladium comprises of dispersed Pd n+ species that are separated by selenium.…”
Section: Resultsmentioning
confidence: 99%
“…The weakening of the interaction of Pt surface atoms with adsorbed hydrocarbon species upon alloying with Sn has been observed in experimental studies. [30][31][32][33][34][35][36]59 The electronic effect of tin on the adsorption of ethylene depends on the type of adsorption site. This dependence has important implications in the observed hydrocarbon chemistry on PtSn alloy catalysts.…”
Section: B Ethylene On Pt"111… and Pt 3 Sn"111…mentioning
confidence: 99%
“…In particular, the interaction of Pt surface atoms with adsorbed hydrocarbon species appears to be weakened by the presence of neighboring Sn atoms. [30][31][32][33][34][35][36] For example, temperature programmed desorption ͑TPD͒ experiments show that desorption maxima are shifted to lower temperatures when Pt was alloyed with Sn. 31,32 Paffett and co-workers 31 have also found that the presence of Sn may alter the nature of the surface species formed on Pt.…”
Section: Introductionmentioning
confidence: 99%